2009
DOI: 10.1007/s00213-009-1508-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ketanserin, buspirone and propranolol on arousal, pupil size and autonomic function in healthy volunteers

Abstract: Ketanserin but not propranolol had a fully sedative profile and may confound pupillometric assessment of EDS. Beta adrenergic receptors do not appear to participate in arousal and pupillary functions, while 5HT1a receptors reduce pupil size without affecting arousal. Pupil size may not be used unequivocally as an index of the level of alertness in the case of drug-induced changes, when drugs interfere with the central pupil control mechanism in ways that are unrelated to their effects on arousal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
11
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
6
11
1
Order By: Relevance
“…For this reason it’s impossible to compare our results (lower light/darkness ratio, lower FHO/RP ratio in infrared light, lower pupil size in yellow-green light, greater pupil size in darkness of TMD group) apparently in disagreement with above cited [42], [50] using light reflex. Moreover, we didn’t use psychometric scales to measure mood and psychological characteristics of subjects.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…For this reason it’s impossible to compare our results (lower light/darkness ratio, lower FHO/RP ratio in infrared light, lower pupil size in yellow-green light, greater pupil size in darkness of TMD group) apparently in disagreement with above cited [42], [50] using light reflex. Moreover, we didn’t use psychometric scales to measure mood and psychological characteristics of subjects.…”
Section: Discussioncontrasting
confidence: 71%
“…Dilator muscle contraction is mediated by alpha-adrenergic receptors and inhibition or relaxation may be exercised by muscarinic receptors and, although not yet fully documented, by beta-adrenergic innervations [46], [47], [48], [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…Mydriasis has been consistently described for DMT (Rosenberg et al 1963;1964;, whereas myosis has been observed for the 5-HT 2 antagonist ketanserin (Koudas et al 2009). Increases in pupillary diameter were reported for ayahuasca by Callaway et al (1999), who administered a lower dose (0.48 mg DMT/kg) and compared changes vs. baseline values, and by Santos et al (in press) for a higher 1.0 mg DMT/kg dose.…”
Section: Discussionmentioning
confidence: 96%
“…Future studies could further explore the discriminative stimulus effects of tramadol using alternative and more complex designs. It is possible that the monoamine reuptakeinhibition activity of tramadol influenced miotic effects because serotonergic drugs also produce miosis (Fanciullacci, Sicuteri, Alessandri, & Geppetti, 1995;Koudas et al, 2009). The use of double-dissociation techniques that also block tramadol's nonopioid effects (e.g., monoamine reuptake-inhibition activity) would help clarify these mixed-action effects and the relationship with miosis.…”
Section: Discussionmentioning
confidence: 99%